Influence of some structural parameters on the dielectric behavior of materials for textile antennas - Loss, Caroline (2018)
Knowledge of the electromagnetic properties of textile materials is crucial in order to design wearable antennas. Despite the growth of research studies on textile antennas, the accurate characterization of the dielectric properties of the materials is still a challenge due to the intrinsic inhomogeneity and deformability of textiles. In this work, 11 textile materials were characterized using the resonator-based experimental technique. The results obtained using this method have shown that when positioning the roughest face of the Material Under Test (MUT) in contact with the resonator board, the extracted dielectric constant (ɛr) value is lower than the one extracted with this face positioned upside-down. Based on this observation, superficial properties of textiles were investigated. Thus, this paper relates the results of the dielectric characterization to some structural parameters of textiles, such as surface roughness and surface and bulk porosity. The results show that both surface roughness and surface porosity of the samples influence the measurements, through the positioning of the probes. Further, the influence of the positioning of the dielectric material on the performance of textile microstrip antennas was analyzed. For this, 12 prototypes of microstrip patch antennas were developed and tested. The results show that, despite the differences obtained in the characterization when placing the face or reverse-sides of the MUT in contact with the resonator board, the obtained average result of ɛr is well suited to design antennas, ensuring a good performance.